Perchlorate in Year‐Round Antarctic Precipitation - S. Jiang; G. Shi; J. Cole‐Dai; M. Wang; Y. Li; G. Wu; C. An; B. Sun (Geophysical Research Letters, 2023)
Abstract Year‐round precipitation in coastal East Antarctica and Antarctic Peninsula was used to investigate the seasonal patterns in sources of atmospheric perchlorate (ClO4−). Although featuring distinct climates, the two locations exhibit similar annual mean and seasonal cycles of ClO4− concentration, with higher values in autumn and lower concentrations in winter and spring. Tropospheric formation dominates atmospheric ClO4− in spring and summer, which is influenced by both oxidants levels and environmental conditions (e.g., air humidity). Tropospheric ClO4− production may also be promoted by elevated levels of oxidants brought by air mass from the interior Antarctic ice sheet in spring and summer. The autumn concentration maximum may originate from ClO4− produced in the stratosphere through reactions between reactive chlorine and ozone during spring and summer. In winter, the stratospheric input may contribute to ClO4− via polar stratospheric clouds sedimentation.